2017
DOI: 10.5114/amsad.2017.70504
|View full text |Cite
|
Sign up to set email alerts
|

No effect of vitamin D supplementation on cardiovascular risk factors in subjects with metabolic syndrome: a pilot randomised study

Abstract: IntroductionPatients with metabolic syndrome (MetS) may have lower 25-hydroxyvitamin D (25(OH)VitD) serum levels compared with non-MetS individuals. Vitamin D (VitD) deficiency is associated with various cardiovascular disease (CVD) risk factors. Yet, the effect of VitD supplementation on MetS remains uncertain. Our aim was to examine the effect of VitD supplementation on CVD risk factors in MetS subjects.Material and methodsThis pilot study had a PROBE (prospective, randomised, open-label, blinded end-point) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 65 publications
0
49
0
1
Order By: Relevance
“…Systolic blood pressure was not reduced by a mere 3.7% in the VitD group. In conclusion, VitD supplementation did not impact on CV disease risk factors in patients with metabolic syndrome [75].…”
Section: Antioxidant Therapy Vitamin D Supplementation and Blood Limentioning
confidence: 72%
“…Systolic blood pressure was not reduced by a mere 3.7% in the VitD group. In conclusion, VitD supplementation did not impact on CV disease risk factors in patients with metabolic syndrome [75].…”
Section: Antioxidant Therapy Vitamin D Supplementation and Blood Limentioning
confidence: 72%
“…Observational studies assessing the association between vitamin D status in patients with MetS and predictive factors, as well as RCTs carried out with vitamin D supplementation, have shown controversial results. In both types of studies, there is no evidence that the lower levels of vitamin D observed in patients with MetS were a cause or a consequence of MetS, or if vitamin D supplementation had benefit across all components of MetS [ 12 , 14 , 16 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have indicated an association between vitamin D deficiency and the onset and progression of T2D as well as future macrovascular events. 7,8 Moreover, in vivo and in vitro studies have proposed potential roles of vitamin D in glucose metabolism, e.g., stimulating insulin secretion via the vitamin D receptor on pancreatic β cells; modulating immune responses and lowering systematic inflammation; and reducing peripheral insulin resistance through vitamin D receptors in the muscles and liver. 11 However, evidence from interventional studies at a population level have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D correction, therefore, may increase insulin secretion and improve glucose homeostasis; however, its effects on healthy individuals or in those with impaired glucose tolerance remain unclear. 6,7 In this study, we wish to determine the metabolic effects of oral vitamin D supplementation in a cohort of T2DM subjects. This study may reveal whether oral vitamin D supplementation can be an adjunct therapy in T2DM patients, and on the importance of optimizing vitamin D levels in the prevention and improved management of T2DM.…”
mentioning
confidence: 99%